Pengembangan Modul Ajar Berbasisi Project Based Learning Berorientasi Teaching at the Right Level dalam Meningkatkan Motivasi Belajar dan Kemampuan Berpikir Kreatif Siswa Kelas X SMK Negeri 1 Gunungsari - Nurul Aini; Ahmad Muzaki; Yuntawati Yuntawati (Jurnal Kependidikan Ki Hajar Dewantara, 2025)
The purpose of this study was to describe how the application of contextual teaching and learning approach in improving students' mathematical connection ability at SMAN 1 Lingsar. This type of research is a classroom action research consisting of two cycles, each cycle consists of four stages, namely planning, action, observation and reflection. The subjects in this study were students of class X IPA 1 SMAN 1 Lingsar which amounted to 37 people consisting of 20 women and 17 men. Data collection was done by using evaluation test (post-test) which includes indicators of students' mathematical connection ability, namely connections between mathematics topics and connections between mathematics in everyday life. The test results of students' mathematical connection ability in cycle I with a percentage of classical completeness of 51.72% and increased in cycle II by 65.62% which was measured using two indicators, so it can be said that there was an increase in students' mathematical connection ability from cycle I to cycle II. Although it did not meet the criteria for classical completeness of 70%, this research was stopped in cycle II due to time constraints and school conditions that had begun to carry out even semester final exams.Keywords: Contextual Teaching and Learning approach and mathematical connection ability